(untitled) (The Review of Diabetic Studies, 2024)
Background: Critically ill patients experience rapid physiological deterioration that demands coordinated multidisciplinary care. Modern critical care extends beyond the ICU, incorporating early detection of clinical decline, advanced organ support, structured referral pathways, and post‑ICU rehabilitation. Surgical, medical, and allied health teams play essential roles in ensuring continuity, stabilization, and recovery. Aim: To provide an updated, comprehensive review of multidisciplinary management strategies for critically ill patients across the continuum of care—from early recognition and ICU admission to organ support and long‑term recovery. Methods: This narrative review synthesizes contemporary evidence and clinical practices described across major domains of critical care: organizational design, referral criteria, levels of care, postoperative surgical management, organ support (respiratory, cardiovascular, renal, neurological, gastrointestinal), sepsis management, delirium prevention, early mobilization, and post‑ICU follow‑up. The review integrates physiological principles, established care bundles, and current international guidelines. Results: Multidisciplinary collaboration improves early recognition of patient deterioration, enhances diagnostic precision, and enables timely intervention. Structured ICU systems—with levels of care, rapid response teams, targeted bundles, and advanced monitoring—optimize outcomes across respiratory, cardiovascular, renal, and neurological domains. Evidence supports early sepsis treatment, lung‑protective ventilation, restrictive transfusion strategies, and early mobilization. Post‑ICU recovery services significantly reduce readmissions and long‑term disability. Conclusion: An integrated, system‑wide approach is essential for managing critically ill patients. Early recognition, coordinated multidisciplinary involvement, evidence‑based organ support, and structured follow‑up collectively reduce morbidity, mortality, and long‑term impairment. Critical care must extend beyond ICU walls, emphasizing prevention, communication, and patient‑centered decision making.